Proangiogenic tumor proteins as potential predictive or prognostic biomarkers for bevacizumab therapy in metastatic colorectal cancer. Issue 3 (24th January 2014) - Bruhn, Maressa A.; Townsend, Amanda R.; Khoon Lee, Chee; Shivasami, Aravind; Price, Timothy J.; Wrin, Joe; Arentz, Georgia; Tebbutt, Niall C.; Hocking, Christopher; Cunningham, David; Hardingham, Jennifer E.; on behalf of the BHI in collaboration with AGITG
<x xml:space="preserve">Abstract</x> Tumor biomarkers to more accurately predict a patient's response to a given therapy are much needed in oncology practice. For metastatic colorectal cancer the anti‐vascular endothelial growth factor (VEGF) monoclonal antibody bevacizumab is now commonly included in first‐line therapy regimens and has led to modest but significant improvements in patient outcomes compared with chemotherapy. Given the modest gains there is a pressing need for predictive biomarkers to better identify patients who would benefit from this targeted therapy. We used a multiplex protein assay to determine the tumor expression levels of the proangiogenic proteins IL‐6, IL‐8, bFGF, PDGF‐BB and VEGF‐A in formalin‐fixed paraffin‐embedded tumors from the MAX clinical trial patients with available tissue samples. Patients were dichotomized into "low" vs. "high" expression subgroups based on median baseline levels to correlate with objective response rate (ORR), progression‐free survival (PFS) and overall survival (OS). "Low" tumor VEGF‐A level was predictive of better ORR for bevacizumab [ORR (low) 53% vs. (high) 19%, interaction p = 0.03] but not for PFS [hazard ratio, HR (low) 0.73 vs. (high) 0.62, interaction p = 0.68] in the comparison of capecitabine (C) versus C and bevacizumab (CB) and CB plus mitomycin (M). When analyzed as a dichotomized variable, "high" VEGF‐A was prognostic for shorter PFS (unadjusted HR 1.34, p = 0.06; adjusted HR 1.55, p = 0.008). The other four proteins were neither predictive of bevacizumab benefits nor prognostic for ORR, PFS or OS. "Low" tumor VEGF‐A was associated with longer PFS after adjustment for other baseline factors. Proangiogenic proteins were not predictive of benefit with bevacizumab for PFS.